Diet and physical activity in the treatment of obesity - current knowledge - Brzuszkiewicz, Kinga; Rudziński, Gracjan; Pożarowska, Kinga; Grunwald, Arkadiusz (Journal of Education, Health and Sport, 2022)
Introduction: Obesity is now becoming a growing problem and challenge for medicine. The number of people with excessive body weight has now reached more than 2 billion, or about 30% of the world’s population. The purpose of this article is to identify and describe some of the already known treatments for obesity, along with the latest research on the subject, in order to show the importance of developing and introducing new methods of weight loss. Aim of the study: The purpose of this article is to review the impact of obesity on health and the diets offered to people struggling with the disease. Materials and methods: We reviewed the literature available in the PubMed database up to November 2022, using the keywords. Results: Consistently limiting caloric intake is a must when losing weight. There are also diets such as low-carbohydrate, low-fat and high-protein diets, but following them can also have some side effects. For example, a high-protein diet can lead to kidney stones. The Mediterranean diet is also a good option for people with obesity. It lowers the risk of cardiovascular disease and cancer. All obesity treatment suggestions consistently recommend a balanced and low-calorie diet with reduced fat (along with saturated fatty acids) and optimal amounts of fiber. In addition to diet, physical activity is an important topic. The primary recommendation for people with obesity is at least moderate to vigorous physical activity of at least 150 minutes per week. Summary: In conclusion, the overarching goal of obesity treatment is to improve quality of life. Calorie restriction, regular exercise or a combination of both is accepted as an effective strategy for preventing or treating obesity.